2012
DOI: 10.1590/s0100-69912012000200005
|View full text |Cite
|
Sign up to set email alerts
|

Emprego do escore MELD para a predição da sobrevivência pós-transplante hepático

Abstract: . We used analysis of area under ROC (receiver operating characteristic) as a summary measure of the performance of the MELD score and assessed predictors of medium-term survival using univariate and multivariate analysis. Results Results ResultsResults Results: The cumulative survival of three, six, 12 and 24 months of the 208 patients studied was 85.1%, 79.3%, 74.5% and 71.1%, respectively. The preoperative MELD score showed a low discriminatory power for predicting survival after TH. By univariate analysis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 38 publications
1
7
0
1
Order By: Relevance
“…Results have shown that a pre-LT MELD of 26 has been associated with worse survival in short-and long-term (10 years) post-LT 19 . Studies conducted in Brazil, such as those by Brandão et al 13 and Batista et al 15 Freitas et al 14 Aranzana et al 18 compared, in a cohort of 164 patients with HCC (16.3%), the areas under ROC curve for post-transplant survival for MELD score at one year and two years after transplantation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Results have shown that a pre-LT MELD of 26 has been associated with worse survival in short-and long-term (10 years) post-LT 19 . Studies conducted in Brazil, such as those by Brandão et al 13 and Batista et al 15 Freitas et al 14 Aranzana et al 18 compared, in a cohort of 164 patients with HCC (16.3%), the areas under ROC curve for post-transplant survival for MELD score at one year and two years after transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…One study (0.6%) was excluded because it was a duplicate. At the end, six articles (3.7%) were eligible for the qualitative analysis (Table 1) [13][14][15][16][17][18] .…”
Section: Eligible Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood transfusion is also linked to reduced survival after transplantation 2 , 11 , with an association between multiple transfusions and complications seen as a predictor of survival 3 . …”
Section: Discussionmentioning
confidence: 99%
“…The need for blood transfusion may also be related to the severity of the condition of the patient at the time of the transplant surgery, in which cases a lower survival rate was already expected 2 , 19 .…”
Section: Discussionmentioning
confidence: 99%